Meat Quality, Intestinal Microbiology and Serum Biochemical Parameters of Broilers Fed Different Levels of Green Tea (Camellia sinensis) and Mulberry (Morus alba) Leaves Powder - Fatemeh Aziz‐Aliabadi; Hadi Noruzi; Ahmad Hassanabadi (Veterinary Medicine and Science)
ABSTRACT Background Today, customers pay more attention to the feed composition and carcasses of poultry, and the interest in using natural and safe compounds such as medicinal plants and their extracts in animal feed is increasing. Objectives The present experiment was conducted to assess the effect of green tea (Camellia sinensis) and mulberry (Morus alba) leaves powder on the meat quality, intestinal microbiology and serum biochemical parameters in broilers. Methods The experiment was conducted with 648 one‐day‐old Ross 308 broiler male chicks with a factorial arrangement including three levels of green tea powder (GTP) and three levels of mulberry leaf powder (MLP), with nine treatments and six replications in a completely randomized design for 42 days. Treatments included: (1) no GTP + no MLP (control), (2) 1% GTP + no MLP, (3) 2% GTP + no MLP, (4) no GTP + 1% MLP, (5) 1% GTP + 1% MLP, (6) 2% GTP + 1% MLP, (7) no GTP + 2% MLP, (8) 1% GTP + 2% MLP and (9) 2% GTP + 2% MLP. Results The results showed that the lowest lightness (L*), drip loss and total cholesterol levels, and the highest Lactobacillus population were observed in treatments: 1% GTP + no MLP, 2% GTP + no MLP, 1% GTP + 1% MLP, 2% GTP + 1% MLP, no GTP + 2% MLP, 1% GTP + 2% MLP and 2% GTP + 2% MLP (p < 0.05). The groups receiving 1% GTP + 1% MLP, 2% GTP + 1% MLP, no GTP + 2% MLP, 1% GTP + 2% MLP and 2% GTP + 2% MLP had the highest pH 24 h (p < 0.05). The chickens fed with 1% and 2% GTP showed lower low‐density lipoprotein cholesterol (LDL) and malondialdehyde (MAD) levels (p < 0.05). Conclusions The results showed that using the GTP and MLP in the diet of broilers could improve meat quality traits and beneficial ileal bacteria populations and reduce serum lipid and MDA levels.